Ideas, machines, and values an introduction to science, technology, and society studies - Cutcliffe, Stephen H. (Rowman & Littlefield Publishers, 2000)
This text is intended as an introductory overview of the emergence of Science, Technology and Society Studies (STS) as a field of study, as well as a summary of interests and concerns.